Papel do imunorreceptor CD300a na inflamação articular em camundongos - Bruno Vinicius Santos Valiate (2017)
Rheumatoid arthritis is an inflammatory autoimmune disease that affects around 1% of the world population, and is more common in women. The maintenance of homeostasis requires balance between activation and inhibition of inflammatory signals in order to avoid tissue damage and chronic inflammation. The receptors that mediate the inhibition signals have ITIM motifs in their cytoplasmic portion, that when phosphorylated, recruit and activate phosphatases that act by dephosphorylating diverse molecules that act as activation signals. Receptor CD300a is an example of inhibitory receptor and expressed in both, lymphoid and myeloid cells. Our aim was to study receptor CD300a in arthritis. We used an antigen induced arthritis (AIA) model and mice lacking the CD300a gene. WT and KO mice were immunized intradermally with 500 g of mBSA in 100L of a saline/FCA (1:1) emulsion. After 14 days, the mice where challenged with 10 g of mBSA in 10 L of saline, directly into the tibiofemoral articular cavity. After 24 hours, the inflammatory parameters were analyzed. When compared to the WT mice, CD300a mice presented an increased number of total cells, mainly polymorphonuclear leukocytes, besides an increased level of CXCL1, IL-6 and MPO activity. We didn’t find a role for CD300a in the resolutory process of our model. CD300a macrophages were more activated than the WT ones as they produced higher quantities of CXCL1 and IL-6. CD300a neutrophils presented an increased capacity to respond to chemotactic agents compared to WT neutrophils, but it cannot be explained by GPCRs desensitization process. Besides not having any difference in the response of B cells from CD300a and WT mice, the splenocytes from the CD300a mice are more activated, thus producing an increased amount of IFN- and IL-17, while secreting less amount of IL-10. Our results show that CD300a has an important role in the control of the inflammatory response in an AIA model, and that it can be an important therapeutic target that regulates exacerbated inflammation.